Eficiência energética de um trator agrícola em função da pressão de inflação dos pneus - Monteiro, Leonardo de Almeida (2013)
The tire inflation pressure, among other factors, determines the efficiency in which a tractor can exert traction. It was studied the effect of using two tire inflation pressures, 110.4 kPa in the front and rear wheels, 124.2 kPa in the front wheel and 138 kPa in the rear wheels, the energetic efficiency of an agricultural tractor of 147 kW of engine power, in the displacement speed of 6.0 km.h-1, on track with firm surface, with the tractor engine speed of 2000 rpm. For each condition of the tire pressure, the tested tractor was subjected to constant forces in the drawbar of 45 kN and 50 kN, covering 30 meters. It was used a randomized complete block with a 2x2 factorial arrangement (tire pressure and drawbar power) with four replications, totaling 16 experimental units. Data were subjected to analysis of variance, using the Tukey test at 5% probability for comparison averages. The lowest hourly and specific fuel consumption, the lowest slippage of the wheelsets and the highest efficiency in the drawbar was obtained with the tire inflation pressure of 110.4 kPa in the front and rear tires of the tractor, highlighting that lower pressures improve energetic and operational performance of the tractor.